Key technologies of smart home network based on G.hn - Dongdi XIAO; Wenda YING; Tao GUO (Dianxin kexue)
In the future smart home,intelligent network high-speed home networking become the trend.Based on this,firstly the modulation and bandwidth of G.hn protocol and the current frequency coaxial cable usage were analyzed.Then the key technology of the G.hn spread spectrum technology was studied.Finally the key points and direction of spread spectrum technology were put forward.